2016
DOI: 10.1093/pm/pnw247
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Chronic Low Back Pain in the Older Adult–Step by Step Evidence and Expert-Based Recommendations for Evaluation and Treatment: Part XI: Dementia

Abstract: Comprehensive pain evaluation for older adults in general and for those with CLBP in particular requires both a medical and a biopsychosocial approach that includes assessment of cognitive function. A positive screen for dementia may help explain why reported pain severity does not improve with usual or standard-of-care pain management interventions. Pain reporting in a person with dementia does not always necessitate pain treatment. Pain reporting in a person with dementia who also displays signs of pain-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It has been suggested that clinicians should consider assessing the cognitive function of older adults with LBP if patients have a known history of dementia, self or family report of memory loss, difficulty in providing details of LBP history that requires supplementary input from caregivers, age above 85 years, or inconsistency between observed pain behaviors and self-reported pain [ 212 , 213 , 218 ]. Some dementia screening tools (e.g., Montreal Cognitive Assessment [ 219 ], Mini-Cog [ 220 , 221 ], and Saint Louis University mental status examination [ 222 ]) have been recommended based on their psychometric properties, ease of use, and accuracy in identifying people with dementia [ 223 ]. Patients with positive screening results should be referred to subspecialty dementia experts (e.g., neurologists, geriatricians, or geriatric psychiatrists) for formal dementia evaluation in addition to LBP treatment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that clinicians should consider assessing the cognitive function of older adults with LBP if patients have a known history of dementia, self or family report of memory loss, difficulty in providing details of LBP history that requires supplementary input from caregivers, age above 85 years, or inconsistency between observed pain behaviors and self-reported pain [ 212 , 213 , 218 ]. Some dementia screening tools (e.g., Montreal Cognitive Assessment [ 219 ], Mini-Cog [ 220 , 221 ], and Saint Louis University mental status examination [ 222 ]) have been recommended based on their psychometric properties, ease of use, and accuracy in identifying people with dementia [ 223 ]. Patients with positive screening results should be referred to subspecialty dementia experts (e.g., neurologists, geriatricians, or geriatric psychiatrists) for formal dementia evaluation in addition to LBP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Since people with moderate to severe dementia may display agitation, anxiety, or nonverbal pain behaviors (e.g., grimacing, yelling, hitting, or bracing), failure to detect pain as a potential cause of agitation may result in unnecessary prescription of anxiolytics or antipsychotics [ 224 ]. As such, proper procedures for evaluating nonverbal dementia patients should include: using a validated observational assessment tool to evaluate pain behaviors during rest and painful conditions/procedures, seeking surrogate report of pain behaviors, and monitoring responses following an analgesic trial [ 223 ]. Since the prevalence of dementia in people aged 85 or older can be as high as 50% [ 218 ], family members or informants are recommended to accompany these patients to meet health-care providers so as to provide detailed pain information [ 223 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of recently published review articles entitled “Deconstructing Chronic Low Back Pain in the Older Adult—Step‐by‐Step Evidence and Expert‐Based Recommendations for Evaluation and Treatment” offered strategies to provide rational care for older adults with chronic LBP. However, expert‐based recommendations presented in this series of articles need to be evaluated through CTs.…”
mentioning
confidence: 99%